Isolation of Uncultured Bacteria from Antarctica Using Long Incubation Periods and Low Nutritional Media - Pulschen, Andre A.; Bendia, Amanda G.; Fricker, Ashwana D.; Pellizari, Vivian H.; Galante, Douglas; Rodrigues, Fabio (Frontiers in Microbiology, 2017)
Uncultured microorganisms comprise most of the microbial diversity existing on our planet. Despite advances in environmental sequencing and single-cell genomics, in-depth studies about bacterial metabolism and screening of novel bioproducts can only be assessed by culturing microbes in the lab. Here we report uncultured, or recalcitrant, microorganisms from an Antarctic soil sample, using relatively simple methods: oligotrophic media, extended incubation periods, observation under stereo microscopy, and selection of slow-growing bacteria. We managed to isolate several rare microorganisms belonging to infrequently isolated or recently described genera, for example Lapillicoccus, Flavitalea, Quadrisphaera, Motilibacter, and Polymorphobacter. Additionally, we obtained isolates presenting 16S rRNA sequence similarity ranging from 92.08% to 94.46% with any other known cultured species, including two distinct isolates from the class Thermoleophilia, that although common in Antarctic soils (as identified by metagenomics), was never reported to be isolated from such samples. Our data indicates that simple methods are still useful for cultivating recalcitrant microorganisms, even when dealing with samples from extreme environments.